2021
DOI: 10.4049/immunohorizons.2100022
|View full text |Cite
|
Sign up to set email alerts
|

Specific COVID-19 Symptoms Correlate with High Antibody Levels against SARS-CoV-2

Abstract: Lasting immunity will be critical for overcoming COVID-19. However, the factors associated with the development of high titers of anti-SARS-CoV-2 Abs and how long those Abs persist remain incompletely defined. In particular, an understanding of the relationship between COVID-19 symptoms and anti-SARS-CoV-2 Abs is limited. To address these unknowns, we quantified serum anti-SARS-CoV-2 Abs in clinically diverse COVID-19 convalescent human subjects 5 wk (n 5 113) and 3 mo (n 5 79) after symptom resolution with th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 42 publications
4
25
0
1
Order By: Relevance
“…This ELISA was not as strong as the anti-RBD assay, given the AUC of 0.919 (Wald 95% CI 0.879, 0.959), sensitivity of 91%, and specificity of 88% (Figure 1D). The lower accuracy of this test is consistent with previous reports with different anti-nucleocapsid tests and may be due to inconsistent immune responses to SARS-CoV-2 nucleocapsid in COVID-19 convalescent subjects and cross-reactivity with the nucleocapsid of common cold coronaviruses 3,6,7,14,15 . Nonetheless, as expected, there was no difference in anti-nucleocapsid IgG levels between naïve versus vaccinated subjects or between 12 month COVID-19 convalescent vaccinated versus unvaccinated subjects (Figure 1E).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This ELISA was not as strong as the anti-RBD assay, given the AUC of 0.919 (Wald 95% CI 0.879, 0.959), sensitivity of 91%, and specificity of 88% (Figure 1D). The lower accuracy of this test is consistent with previous reports with different anti-nucleocapsid tests and may be due to inconsistent immune responses to SARS-CoV-2 nucleocapsid in COVID-19 convalescent subjects and cross-reactivity with the nucleocapsid of common cold coronaviruses 3,6,7,14,15 . Nonetheless, as expected, there was no difference in anti-nucleocapsid IgG levels between naïve versus vaccinated subjects or between 12 month COVID-19 convalescent vaccinated versus unvaccinated subjects (Figure 1E).…”
Section: Resultssupporting
confidence: 89%
“…Demographic and clinical information were collected by questionnaire and abstraction of the electronic medical record. COVID-19 severity was diverse with mild (n=12), moderate (n=86), severe (n=15) and critical (n=8) clinical phenotypes represented as previously defined 14 . Subjects provided blood and clinical information 5 weeks (n=121), 3 months (n=115), 6 months (n=98) and 12 months (n=100) after symptom resolution.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…This is in contrast to the study conducted by Lynch et al who demonstrated that SARS-CoV-2 antibody responses were significantly higher in patients with a severe compared to a milder disease course [ 50 ]. Another study showed that as well as severity of disease course, specific COVID-19 symptoms, namely fever, body aches and low appetite, might go along with a higher antibody response [ 51 ]. However, a direct comparison of those studies with our data is difficult as participant cohorts differed substantially with regard to symptoms and disease course.…”
Section: Discussionmentioning
confidence: 99%
“…In general, SARS-CoV-2 antibody levels are higher in patients with a severe disease outcome ( 14 ). A recent study in which COVID-19 convalescent plasma (CCP) donors were followed for three months after symptom resolution showed that greater disease severity, older age, male sex, and high BMI correlate with high SARS-CoV-2 antibody levels ( 7 , 15 ). The same study also reported that particularly the symptoms fever, body aches, and low appetite correlate with high SARS-CoV-2 antibody levels.…”
Section: Introductionmentioning
confidence: 99%